Two new genera of neotropical Deltocephalinae (Insecta: Homoptera: Cicadellidae) related to Alaca Oman - Lozada, Pedro (1998)
Two new genera of Neotropical Deltocephalinae (Insecta: Homoptera: Cicadellidae) related to Alaca Oman: Paralaca gen. n. and Adlaca gen. n., and two new species, P. sordida and A. dubiosa, from Manu Reserved Zone, Southeastern Peru, are described and illustrated herein. A key to these three closely related genera is presented.